An Approach to Conductivity Hydraulic Value for Known Soil Types as Pre Eliminate for Water Pre Treatment - Yulfiah; Maritha Nilam Kusuma (Nusantara Science and Technology Proceedings)
Water treatment in Indonesia still used coagulant to reduce contaminant. So that, needing pre-treatment before conventional water treatment, use infiltration gallery. Infiltration gallery is the one of natural technology for absorbing or filtration contaminant. The main role in filtration of contaminate in soil is conductivity hydraulic. There are many kind of soil type with different conductivity hydraulic. In infiltration gallery method we need to know conductivity hydraulic value as preliminary analysis. Because its ability is make movement water from one side to other side, while filtrate the contaminant. Slower conductivity, it is mean that the quality water will be good. The methods used is constant head each permeameter. The result we get, was soil type in same type have different conductivity hydraulic.